Low-dose bevacizumab induces radiographic regression of vestibular schwannomas in neurofibromatosis type 2: A case report and literature review - LIU, PENGFEI (Oncol Lett, 2016)
The current case study aimed to explore the efficacy of a low-dose bevacizumab regimen in inhibiting tumor growth and minimizing adverse effects. A 55-year-old man with neurofibromatosis type 2 (NF2) suffered bilateral vestibular schwannomas (VS) measuring 5.25 and 2.54 cm(3) on the left and right, respectively. His capacity for bilateral language recognition was impaired. However, the patient refused microsurgical tumor resection and gamma knife therapy. Low-dose bevacizumab regimen (3.3–2.2 mg/kg every 2–4 weeks) was administered by intravenous injection for ~1.5 years to inhibit tumor growth and avoid further deterioration of hearing. Compared with baseline measurements prior to treatment, the bilateral VS regressed to 3.59 cm(3) (68%) and 2.08 cm(3) (82%) on the left and right, respectively. No hearing improvement was detected; however, the patient subjectively experienced a significant hearing improvement as his ability to communicate with people and distinguish voices was restored. No adverse effects were observed. Bevacizumab provides an alternative treatment option for those who refuse surgical intervention. Given the adverse effects commonly induced by bevacizumab, the use of a low-dose regimen would appear to be promising with regard to tumor regression and hearing preservation for patients with VS in NF2. However, the minimum dose required to sustain a response to bevacizumab in NF2 patients remains unknown. Finding the minimum effective dose sufficient to sustain hearing and/or volumetric response for individual patients is required.